Aspectos toxicológicos de paration metílico e de extrato aquoso de folhas secas de nim (Azadirachta indica) para o pacu (Piaractus mesopotamicus) e eficácia no controle de monogenea Dactylogyridae - Cruz, Claudinei da [UNESP] (2005)
The objectives of the present study were 1) to determine the 50% lethal concentration (LC (l)50-96h) of methyl parathion and azadirachtin present in the aqueous extract of dry neem leaves (AEDNL) for pacu (Piaractus mesopotamicus), 2) to evaluate the efficacy, safe concentrations and exposure time of methyl parathion and azadirachtin for the control of Anacanthorus penilabiatus, 3) to assess the alterations that occur in the gills and liver of fish exposed to sublethal concentrations of methyl parathion and azadirachtin, and 4) to determine the presence of azadirachtin residues in pacu (Piaractus mesopotamicus) by high-performance liquid chromatography HPLC. The calculated LC (l) 50-96h of methyl parathion was 3.97 mg/L for fry pacu and 9.89 mg/L for juvenile fish. The LC (l) 50-96h of azadirachtin present in AEDNL was 1.20 and 1.18 mg/L for fry and juvenile fish, respectively. Methyl parathion was less toxic to fry and juvenile pacu than azadirachtin. In gills, methyl parathion caused congestion, lamellar fusion, subepithelial edema, interstitial hemorrhage, and disorganization of the lamellar structure, whereas azadirachtin caused subepithelial edema and apical fusion of secondary lamellae. In the liver, methyl parathion caused congestion, cell fusion, hepatocyte hyperplasia and derangement of the cord-like organization of hepatocytes, and azadirachtin caused disorganization of the cord-like arrangement of hepatocytes, cytoplasmic vacuolization, and necrosis of epithelial cells lining the bile canaliculi. Methyl parathion was more effective than the AEDNL in the control of monogenetic parasites, with this control being proportional to the increase of the insecticide's concentration in water and of exposure time. The highest efficacy of methyl parathion was observed at a concentration of 7 mg/L, with a 96.2% rate of parasite control after 16 h of exposure and a 97.0% rate after 24 h. For AEDNL, a...